The impact of die angle on tool loading in the process of cold extruding steel - Randjelović, Saša (Materiali in tehnologije, 2012)
This paper presents an analysis of tool loading in the technology of the cold forward extrusion of steel. In the process of plastic deformation it is necessary to know the contact stress as a prerequisite for a more accurate analysis of the stress and strain on the internal structure of the continuum. In this way, accurate boundary conditions at the contact surfaces are obtained for the achieved conditions of deformation, which represent the starting values for generating numerical approximations of the plasticity parameter changes within the deformable volume. In the process of the forward extrusion of steel the workpiece material is exposed to all-round pressure during the entire process. Due to the high surface pressure at the head of the punch and the solid walls of the die, the material flows in the direction of the opening of the exchangeable conical surfaces of the die. During the extrusion process, the greatest resistance occurs in the direction of the axis displacement, i.e., the head punch, while the walls of the tools suffer considerably smaller loads. However, this has crucial importance for the accuracy and the quality of the finished part.
Keywords: cold extrusion; hladna ekstruzija; jeklo; stell; stress; napetosti; deformacije; deformation